The puerperium of quilombola women: the light of Madeleine Leininger's transcultural care (Research, Society and Development, 2021)
Objective: To analyze the factors that influence the care of quilombola women in the puerperium. Method: This is a qualitative study, based on ethno-nursing and the theoretical framework of Madeleine Leininger's Theory of Diversity and Universality of Care, with the objective of describing the care of quilombola women in the postpartum period, emphasizing cultural care and religious in the community. Results: Quilombola women use cultural, empirical and religious knowledge to provide health care. When using the plants, they know what they are using it for, because they specify what type of plant it is, as well as its indication, it is what is observed in the speech of one of the interviewees below, it also makes use of prayers, cures and baths. sun to assist in the recovery process. Conclusion: Studies on different types of care and natural medicine, together with the factors that encompass them, allow a better view of the circumspection of cultural identity and empirical knowledge attributed to the different audiences assisted by health professionals.